ANALISA UJI KINERJA MESIN MESIN PENGGILING BIJI SALAK MENJADI SERBUK DENGAN PEROSES GANDA KAPASITAS 30 KG/JAM - LUBIS, ZULKIFLI (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2017)
Coffee is one of the drinks that many people like, in general, coffee is made from real coffee beans which are processed into powder, it turns out that apart from the original coffee beans can also be made from other ingredients, such as bark which are popular in fruit-producing areas salak. The efficacy of coffee bark that is believed to increase stamina, reduce blood pressure and uric acid by the community, making coffee bark and producing coffee powder of bark is increasingly developing. The machine for grinding bark into powder is a machine used to grind zalacca seeds into powder to be used as bark coffee. The construction of the machine to be tested uses a suction method where the mechanism of bark through the inlet will be directed to a row of counter blades and after being filtered and driven by a thread shaft will pass through a row of fine counters / double processors. This machine will be tested for performance to determine the productivity of the machine such as Capacity (Q), Quality (K) and Power usage (P). The test was carried out using 5 kg of disunrice bark seed raw material with 3 times testing. The test results can be concluded that the maximum capacity of 33 kg / hour occurs the second test and the average machine quality is 94.47%. The maximum engine power of 1,253.3 Watts was obtained at the first test and the minimum power was 1,153.3 Watts on the 2nd test. The energy needed to grind 1 kg of bark into powder ranged from 38.13 W-h/hr.